PENGARUH E-SERVICE QUALITY DAN DISKON TERHADAP MINAT BELI PADA SITUS ONLINE DI WEBSITE Zalora.co.id DI SURABAYA - NASIR, MOH. (Jurnal Pendidikan Tata Niaga (JPTN), 2016)
Zalora is one of the famous online trading sites in Indonesia. It provides various fashion products for men, women, and children, such as clothes, shoes, bags, and accessories. Online trading has been a trend in all around the world, including Indonesia. Thus, in Indonesia, it is a common thing to find companies using internet in marketing their products as well as engaging more customers. To increase the buyers’ purchase intention, Zalora applies various strategies. One of the strategies is e-service quality and discount. E-service quality includes website design, reliability, security or privacy, and customer service. Based on the results of this study show e-service quality and discounts on the website Zalora.co.id in Surabaya. It can be concluded that the e-service quality has positive influence on buying interest at an online site Zalora.co.id website in Surabaya. The better the e-service quality that is provided by the website Zalora hence, the greater the consumer purchase interest in Zalora website. Similarly discount positive effect on buying interest in Zalora website. The bigger the discounts offered, the greater the consumer purchase interest in Zalora website. So we can conclude that e-service quality and discounts jointly positive effect on buying interest on the website Zalora.co.id in Surabaya. Keywords: E-Service Quality, Discounts, Purchase Intention